Do we dream correctly? - Getov, Peter (Leadership, Society, Strategic Visions, 2021)
Over 60 students from Bachelor’s and Master’s programs participated in the competition for the best essay, organized by the Final Scientific and Practical Conference, dedicated to the 25th anniversary of the creation of the fi rst programs in Business Administration in Bulgaria. Foreign students from Greece, Syria, Ukraine and Russia also showed interest in the competition.